Reversible Logic based Cryptography Design Algorithm using Random Keys - Rithiga, S.; Kumar, T. Venish; Idhayachandran, M.; Prathap, S. (Journal of Electronics and Informatics, 2023)
Reversible computations, besides quantum computing, have various applications in digital signal processing, nanotechnology and bioinformatics. They are particularly useful in designing low-power devices and improving computational efficiency. Cryptography is vital for protecting sensitive information in fields such as bioinformatics and digital signal processing where private data is frequently exchanged. However, cryptographic algorithms can consume significant power and require large areas, particularly when implemented in hardware. Reversible logic gates offer a potential solution by being more power-efficient and potentially reducing implementation area. Using random numbers as keys for both encryption and decryption in a reversible logic gate-based cryptographic algorithm can enhance security. LSB watermarking is a technique to embed additional metadata into digital media, improving data security. To evaluate the performance of the Field Programmable Gate Array for the Reversible Logic Gate Cryptography Design architecture, comparing it to the other state-of-the-art approach is necessary.